Photocatalytic degradation of 2,4-dichlorophenoxyacetic acid on N-doped titanium dioxide - Hanh, Nguyen Ngoc; Khoi, Pham Quang; Thao, Vo Huu (Vietnam Journal of Chemistry, 2016)
Photocatalytic degradation, especially hetetogeneous catalytical oxidation is an emerging method for removing organic contaminants in water. TiO2 catalyst with excellent mechanical and thermal properties has been paid much attention. However, TiO2 catalyst suffers from reduced photonic efficiency. In this study TiO2 catalyst has been prepared by sol-gel method and modified in presence of urea by thermal treatment at 450 °C for 1 hour with heating rate of 5 °C/min. This catalyst was used in photocatalytic degradation of 2,4-Dichlorphenoxyacetic acid (2,4-D). The influence of reaction parameters such as radiation source, pH, 2,4-D initial concentration and catalyst content was investigated. Under UVA radiation, with 2,4D solution of 60 ppm at pH 3 and catalyst content of 0.6 g/L, the conversion was of 63 %, but under VIS radiation only about 30 %. Keywords. TiO2, N-doped TiO2, 2,4-Dichlorophenoxyacetic acid, photocatalysis, UVA, VIS.